Titanium Septum Plate: A novel technique to straighten and to stabilize the Nasal Septum using a Modified Titanium Breathe-Implant - Daniel F àWengen (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
Importance: The cartilagineous nasal septum remains a difficult structure to straighten and to stabilize as it tends to bend. Recurrence of an asymmetric and bent septum is a frequent complain in patients as it may lead to asymmetric nasal breathing and/or aesthetic asymmetries of the shape of the nose. Objective: To investigate a novel technique: the implantation of a titanium septum plate (TSP) in its use as a septum stabilizer and straightener. To present a clinical study on the experience of a modified titanium Breathe-Implant used as a septum plate. Design Settings and Participants: In this retrospective study, medical records as well as preoperative and postoperative functional studies in which a titanium septum plate had been used between February 2014 and May 2016 in a total of 31 consecutive patients subjected to septoplasty with the use of one or two Titanium Septum Plates (TSP) in closed and open surgeries by the same surgeon were reviewed. All (100 %) were eligible and included in the study. Interventions: Before surgery, a complete rhinological examination was conducted including nasal endoscopy, digital endonasal photography, rhinomanometry, PNIF mask testing, and a SNOT 20 questionnaire. Results: This is the first report in the literature to use a titanium plate in septoplasty. There were no intra- or postoperative complications in the use of TSP. In all 31 patients all TSP remain in the nose. In the accumulated observational period of 544 months there were no exposures internally or externally, no extrusions, no infections and no explantations. In the usual placement of TSP the implant runs parallel to the axis of the nose. Metal is much stronger than cartilage to straighten the nasal axis. No postoperative infection was observed and no antibiotic prophylaxis or therapy were necessary. Conclusions and Relevance: The implantation of TSP has proven over time to be safe and reliable. Titanium is an inert metal suited for septal surgery. Future implants specifically designed for septoplasty will facilitate septal surgery and will help to achieve more stable long-term results with hopefully better patient satisfaction than septoplasty alone.